Parallel Divide-and-Conquer Algorithms for Bubble Sort, Selection Sort and Insertion Sort. (2nd August 2021) - Ganapathi, Pramod; Chowdhury, Rezaul
Abstract: We present efficient parallel recursive divide-and-conquer algorithms for bubble sort, selection sort, and insertion sort. Our algorithms have excellent data locality and are highly parallel. The computational complexity of our insertion sort is ${{\mathcal{O}}}\left ({n^{\log _2 3}}\right )$ in contrast to ${{\mathcal{O}}}\left ({n^2}\right )$ of standard insertion sort.